Tenascin-X as a causal gene for classical-like Ehlers-Danlos syndrome - Okuda-Ashitaka, Emiko; Matsumoto, Ken-ichi (Frontiers in Genetics, 2023)
Tenascin-X (TNX) is an extracellular matrix glycoprotein for which a deficiency results in a recessive form of classical-like Ehlers Danlos syndrome (clEDS), a heritable connective tissue disorder with hyperextensible skin without atrophic scarring, joint hypermobility, and easy bruising. Notably, patients with clEDS also suffer from not only chronic joint pain and chronic myalgia but also neurological abnormalities such as peripheral paresthesia and axonal polyneuropathy with high frequency. By using TNX-deficient (Tnxb-/-) mice, well-known as a model animal of clEDS, we recently showed that Tnxb-/- mice exhibit hypersensitivity to chemical stimuli and the development of mechanical allodynia due to the hypersensitization of myelinated A-fibers and activation of the spinal dorsal horn. Pain also occurs in other types of EDS. First, we review the underlying molecular mechanisms of pain in EDS, especially that in clEDS. In addition, the roles of TNX as a tumor suppressor protein in cancer progression have been reported. Recent in silico large-scale database analyses have shown that TNX is downregulated in various tumor tissues and that high expression of TNX in tumor cells has a good prognosis. We describe what is so far known about TNX as a tumor suppressor protein. Furthermore, some patients with clEDS show delayed wound healing. Tnxb-/- mice also exhibit impairment of epithelial wound healing in corneas. TNX is also involved in liver fibrosis. We address the molecular mechanism for the induction of COL1A1 by the expression of both a peptide derived from the fibrinogen-related domain of TNX and integrin alpha 11.